2016
DOI: 10.1149/2.1031610jes
|View full text |Cite
|
Sign up to set email alerts
|

Direct Growth of Birnessite-Type MnO2on Treated Carbon Cloth for a Flexible Asymmetric Supercapacitor with Excellent Cycling Stability

Abstract: This paper reports a facile means of fabricating a flexible supercapacitor with excellent cycling stability, based on the use of carbon cloth (CC) activated and subsequently modified with birnessite-type MnO 2 . In this study, sections of commercially-available CC were treated using a simple wet method and then served as substrates for the direct growth of MnO 2 via an electrochemical process. The resulting CC electrodes allowed the deposition of a large amount of MnO 2 while maintaining its electrochemical ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 53 publications
0
12
1
Order By: Relevance
“…Considering the mass loading of NaFePO 4 on CC (0.3 mg ⋅ cm −2 ), the mass specific capacitance of NaFePO 4 /CC//NaPA//AC/CC is 154.43 F ⋅ g −1 at the current density is 3.3 A ⋅ g −1 . This specific capacitance is superior to the reported CoFe 2 O 4 /CFC//PSS//Fe 2 O 3 ‐CNTs/CFC (181.30 F ⋅ g −1 at 1 A ⋅ g −1 ), [31] MnO 2 /CC//AC/CC (133.02 F ⋅ g −1 at 3 A ⋅ g −1 ), [32] Ni 0.85 Se/CFC//KOH/PVA//AC/CFC (81 F ⋅ g −1 at 1 A ⋅ g −1 ), [33] and MnO 2 /Ti 3 C 2 T x /CC//PVA‐LiCl//Ti 3 C 2 T x /CC (60.60 F ⋅ g −1 at 1 A ⋅ g −1 ) [34] . With the specific capacitance of 154.43 F ⋅ g −1 , the energy density of NaFePO 4 /CC//NaPA//AC/CC can be 5.36 Wh ⋅ kg −1 , and the power density reaches 839.31 W ⋅ kg −1 .…”
Section: Resultscontrasting
confidence: 55%
“…Considering the mass loading of NaFePO 4 on CC (0.3 mg ⋅ cm −2 ), the mass specific capacitance of NaFePO 4 /CC//NaPA//AC/CC is 154.43 F ⋅ g −1 at the current density is 3.3 A ⋅ g −1 . This specific capacitance is superior to the reported CoFe 2 O 4 /CFC//PSS//Fe 2 O 3 ‐CNTs/CFC (181.30 F ⋅ g −1 at 1 A ⋅ g −1 ), [31] MnO 2 /CC//AC/CC (133.02 F ⋅ g −1 at 3 A ⋅ g −1 ), [32] Ni 0.85 Se/CFC//KOH/PVA//AC/CFC (81 F ⋅ g −1 at 1 A ⋅ g −1 ), [33] and MnO 2 /Ti 3 C 2 T x /CC//PVA‐LiCl//Ti 3 C 2 T x /CC (60.60 F ⋅ g −1 at 1 A ⋅ g −1 ) [34] . With the specific capacitance of 154.43 F ⋅ g −1 , the energy density of NaFePO 4 /CC//NaPA//AC/CC can be 5.36 Wh ⋅ kg −1 , and the power density reaches 839.31 W ⋅ kg −1 .…”
Section: Resultscontrasting
confidence: 55%
“…As a control sample, the ex-MnO 2 electrode showed significant electron and ion limitations in the thick electrode, resulting in inferior areal capacitance compared to MnO 2 /C. Based on a comparison summary of 19.7-MnO 2 /C and other MnO 2 -based materials with similarly high mass loadings reported in the literature (Figure 4f), [14,29,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] it was concluded that 19.7-MnO 2 /C is a superior high-mass-loading electrode with ultrahigh specific capacitance and impressive rate ability. In addition, the mass loading of 19.7 mg cm −2 fully To demonstrate the superior performance of MnO 2 /C, the charge transfer behavior of the electrodes was investigated by analyzing the electrochemical impedance spectroscopy (EIS) results measured in the frequency range of 0.01-100 kHz.…”
Section: Resultsmentioning
confidence: 91%
“…These values (gravimetric and volumetric capacitances) are considerably higher than the values reported for MnO 2 -based electrodes with substantially smaller loadings of MnO 2 ( Figure 4E; Table S3). 10,15,21,22,38,39 EIS analysis show that the 3D printed G/MnO 2 electrodes with different thicknesses have similar R s and Warburg resistances ( Figure S25; Table S4), reflecting their superior conductivity and ion diffusion efficiency. It explains why, when the electrode thickness increased, the areal capacitance increased almost linearly while retaining the gravimetric and volumetric capacitances.…”
Section: Resultsmentioning
confidence: 99%